2012
DOI: 10.1063/1.4752093
|View full text |Cite
|
Sign up to set email alerts
|

Electrically active magnetic excitations in antiferromagnets (Review Article)

Abstract: The magnetic resonance operation by electric field is highly nontrivial but the most demanding function in the future spin-electronics. Recently observed in a variety of multiferroics materials named the collective electrically active magnetic excitations, frequently referred to as "electromagnons", reveal a possible way to implement such a function. Experimental advances in terahertz spectroscopy of electromagnons in multiferroics as well as related theoretical models are reviewed. The earlier theoretical wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
0
17
1
Order By: Relevance
“…20,22, this form of boundary conditions leaves questions with regard to the microscopic interpretation of the exchange coupling constant * AB A . So, either the natural boundary conditions (8)(9) or the generalized Barnaś-Mills boundary conditions (36)(37) should be used instead.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,22, this form of boundary conditions leaves questions with regard to the microscopic interpretation of the exchange coupling constant * AB A . So, either the natural boundary conditions (8)(9) or the generalized Barnaś-Mills boundary conditions (36)(37) should be used instead.…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to see that the direction of the magnetization becomes continuous if one neglects in equation (16) terms of the order of  a a x     m , where λ is the spin wave wavelength 24 (or any alternative appropriate quantity describing the characteristic length scale of the non-uniformity of the magnetization direction). This assumption (that the spin wave wavelength is greater than lattice constants of constituent materials) is the essence of the continuous medium approximation in magnonics, in which the natural boundary conditions (8)(9) are derived. In particular, this explains why such a continuous medium approach as the plane wave method 70,[74][75][76][77] is consistent with the natural boundary conditions (8-9) but experiences difficulties adopting the notion of the interlayer exchange coupling.…”
Section: Natural Hoffmann and Barnaś-mills Forms Of Magnetizatimentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the dynamic response under oscillating fields can elucidate other significant interactions. Magnetoelectric coupling creates a new quasiparticle excitation-the electromagnon-at terahertz (THz) frequencies [7][8][9][10][11][12][13] . Electromagnons have been discovered in rareearth-doped compounds such as RMnO 3 and RMn 2 O 5 at low temperature (o70 K), and are thought to result from modifications of the Heisenberg exchange interaction 14,15 , which has a S i Á S j term in the spin Hamiltonian.…”
mentioning
confidence: 99%
“…It was found that the application of critical magnetic field of 20 kOe suppressed the polarization P s states along the c-axis whereas it started increasing along the aaxis. [184,186] To confirm the origin and selection rules for these two peaks of TbMnO 3 and DyMnO 3 , light polarization-dependent measurements were performed. [184] Pimenov et al observed the new collective excitation corresponding to this multiferroic state known as electromagnon, i.e., electric-dipole active magnetic excitation in the imaginary part of the THz dielectric constant for GdMnO 3 and TbMnO 3 .…”
Section: Thz Studies On Multiferroic Rmnomentioning
confidence: 99%